The Role of INSR & Diabetes in Polycystic Ovarian Syndrome - Afrouz KHAZAMIPOUR; Azim NEJATIZADEH; Eghbal EFTEKHAARI TASNIM (Tehran University of Medical Sciences, 2018)
The Role of INSR & Diabetes in Polycystic Ovarian Syndrome